ASSESSMENT OF THE QUALITY OF CARE AND TREATMENT FOR ACUTE STROKE PATIENTS IN THE FIRST QUARTER OF 2026 AT THANH HOA GENERAL HOSPITAL - Doan Thi Bich; Le Tri Truong; Ngo Thi Phuong Hoa; Hoang Huu Truong (Tạp chí Y học Quân sự, 2026)
Objective: To evaluate the quality indicators of acute stroke care and treatment during the first quarter of 2026 at Thanh Hoa General Hospital. Methods: A retrospective cross-sectional study was conducted to evaluate the quality management of acute stroke care and treatment at the Department of Neurology and Stroke, Thanh Hoa General Hospital, from January 1 to March 31, 2026. Secondary data obtained from the RES-Q stroke quality registry were used to describe quality indicators and compare them with national RES-Q Vietnam data. Results: A total of 413 patients with acute stroke were admitted during the study period. Male patients accounted for 58.1%, with a median age of 69 years. Hypertension was the most prevalent vascular risk factor (79.2%). Most patients arrived at the hospital by private transportation (94.3%), whereas only 0.3% were transported by emergency medical services from the scene. Among patients with acute ischemic stroke, 17.2% received intravenous thrombolysis and 18.3% underwent mechanical thrombectomy. Median workflow metrics were as follows: door-to-imaging time, 15 minutes (interquartile range [IQR], 10-19); door-to-needle time, 36 minutes; door-to-groin puncture time, 42 minutes for direct admissions and 49 minutes for transferred patients; and door-to-reperfusion time, 93 minutes. These workflow metrics compared favorably with the corresponding benchmark data from the RES-Q Vietnam registry. The primary reason for not receiving intravenous thrombolysis was delayed hospital arrival (61.2%). Functional independence at discharge, defined as a modified Rankin Scale (mRS) score ≤2, was achieved in 59.2% of patients. The in-hospital mortality rate was 5.2%, and post-discharge follow-up appointments were scheduled for 98.5% of patients. Conclusion: Quality indicators of acute stroke care and management at Thanh Hoa General Hospital showed favorable overall performance, particularly in diagnostic workflow and reperfusion therapy metrics. The major limitations were observed in the prehospital phase, including a high rate of delayed hospital presentation and low utilization of emergency medical services from the scene.